IDENTIFY CASES WITH THE TOPIC OF ONLINE LOANS IN THE PERIOD 2020-2024 IN INDONESIA - Sofy Aprillia Lihawa; Sri Budi Purwaningsih (Antis Publisher, 2025)
Objective: This research investigates Supreme Court rulings in Indonesia concerning online loans from 2020 to 2024. Method: The analysis employs empirical methods with a legal research approach, integrating primary data from Supreme Court decisions and secondary data from legal regulations and journal literature. Results: Studied cases encompass civil and criminal classifications, emphasizing disputes in divorce cases and violations of information technology laws. Bibliometric analysis results highlight the complexity of addressing online loan cases in Indonesia within the contexts of justice, and law enforcement. Novelty: This research provides a comprehensive review of Supreme Court rulings on online loans in Indonesia over a recent five-year period, combining civil and criminal perspectives and employing bibliometric analysis to reveal the challenges in legal enforcement and justice.